More Than Hoop Jumping: Making Accreditation Matter (LEARNing Landscapes, 2015)
This study provides a discussion of faculty perspectives on the impact of national accreditation on a teacher education program. Research questions from a three-year investigation examined the influence of accreditation on how teacher educators approach their work and whether meeting accreditation requirements contributes to ongoing, systemic self-reflection. Self-study survey data identified faculty perspectives on the influence of accreditation on planning, instruction, curriculum development, assessment, collaboration, reflection, and awareness of accreditation discussions. Accreditation as a form of self-study reveals both strengths and the inherent challenges of meeting the sometimes competing goals of accreditation requirements and meaningful examinations through self-reflection. Study implications underscore the need for conscious efforts to maintain self-reflection as central to program improvements and considerations for teacher educators’ work.
Keywords: teacher research; teacher education; accreditation; self-study; self-reflection